Seeking menstrual products: a qualitative exploration of the unmet menstrual needs of individuals experiencing homelessness in New York City - Caitlin Gruer; Kim Hopper; Rachel Clark Smith; Erin Kelly; Andrew Maroko; Marni Sommer (BMC, 2021)
Abstract Background There has been increasing recognition that certain vulnerable populations in the United States of America struggle to meet their menstruation-related needs, including people experiencing homelessness. Media and policy attention on this subject has focused on the provision of free menstrual products to vulnerable populations, including a New York City legislative bill, which guarantees access to menstrual products for Department of Homeless Services shelter residents (Intros 1123-A). Methods This qualitative study explored the challenges people experiencing homelessness in New York City face in accessing menstrual products. Data collection was conducted from June to August 2019 and included: Semi-structured key informant interviews with staff from relevant government agencies and homeless service providers (n = 15), and semi-structured in-depth interviews with individuals with experience living on the street and in shelters (n = 22). Data were analysed using thematic analysis. Results Key themes that emerged included: (1) insufficient and inconsistent access to menstrual products; (2) systemic challenges to providing menstrual products; and (3) creative solutions to promote access to menstrual products. Both shelter- and street-living individuals reported significant barriers to accessing menstrual products. While both populations struggle, those in shelters were more likely to be able to purchase menstrual products or access free products at their shelter, while those living on the streets were more likely to have to resort to panhandling, theft, or using makeshift materials in place of menstrual products. Across both populations, individuals described barriers to accessing free products at shelters and service providers, primarily due to distribution systems that rely on gatekeepers to provide a few pads or tampons at a time, sometimes of inadequate quality and only upon request. Shelters and service providers also described challenges providing these products, including inconsistent supply. Conclusion These findings highlight the critical importance of expanding and improving initiatives seeking to provide access to menstrual products for vulnerable populations. Despite policy level efforts to support menstrual product access, individuals experiencing homelessness in New York City, whether living in shelters or on the street, are often not able to access the menstrual products that they need to manage their monthly menstrual flow.